A tale of three seasons: a cultural sport psychology and gender performativity approach to practitioner identity and development in professional football. Issue 5 (3rd September 2021) - Champ, Francesca; Ronkainen, Noora; Tod, David; Eubank, Artin; Littlewood, Martin
ABSTRACT: The present study explored how the organisational and cultural experiences of a trainee Sport Psychology Consultant (SPC) working in professional football shaped her identity and professional development. Drawing on Cultural Sport Psychology (CSP) and gender performativity as guiding frameworks, we explored the first author's identity development as a sport psychology practitioner-researcher within one professional football club over a 3-year duration. Traditional ethnographic data collection methods were employed, including, field notes and a reflective journal. Through creative non-fiction vignettes, we show that the traditional masculine discourse in professional football shaped the first author's sense of self and subsequent behaviours. From the results of this study, we suggest that SPCs identity development is not smooth or linear, rather it can be described as a 'rocky road to individuation' defined by a series of culturally specific 'critical moments'. We strongly believe that contextual intelligence and cultural proficiency are essential for a trainee SPCs survival during early and later career stages of working within elite and professional sport environments.